EDUKASI DALAM PEMANFAATAN DANAU SENTANI YANG RAMAH LINGKUNGAN DAN BERKELANJUTAN BAGI GENERASI MUDA DI KAMPUNG YOBEH DISTRIK SENTANI KOTA KABUPATEN JAYAPURA - Mulyono, Herlina Irianti; Maga, La; Waroi, Heldo Mariche (LPPM Universitas Bina Bangsa, 2025)
The use of non-environmentally friendly natural resources, both renewable and non-renewable natural resources, will have a direct impact on the condition of the environment itself. One of the natural resources that can provide direct benefits to the community is lake water. One of the lakes that has been utilized by the community for both tourism areas and other activities is Lake Sentani. Lake Sentani is greatly influenced by human activities that utilize various existing potentials. Any change to the landscape of Lake Sentani can affect the biodiversity in Lake Sentani. For this reason, real action is needed in an effort to provide education to the community regarding the sustainable utilization of Lake Sentani's potential and its benefits can be enjoyed sustainably. The community around Lake Sentani, especially the younger generation, must have basic knowledge about the environmentally friendly utilization of Lake Sentani. Educational activities are carried out face-to-face using aids in the form of posters. Based on the results of the activities, several conclusions can be outlined, including: (i) Basically, participants already understand several functions of Lake Sentani for the community; (ii) The use of posters as a tool in socialization activities greatly increases enthusiasm and makes it easier for participants to understand the information that can be obtained from a picture; and (iii) Forming discussion groups using aids in the form of posters can improve participants' ability to discuss what information can be taken from the posters.